Leadership of Generation Z Women: A Critical Study of Gender Equality and Islamic Perspectives - Layla, Desteny; Santika, Sovia; Efrinaldi, Efrinaldi; Sulfinadia, Hamda; Amirah, Nabilla; Zufialina, Era (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
This study examines the topic of women’s leadership, which has been a subject of discussion among classical and contemporary scholars, intellectuals, and the general public. The relevance of this discourse grows when viewed in the context of Generation Z, a generation shaped by rapid technological advancements. The study seeks to analyze the characteristics of Generation Z, the concept of women’s leadership, and perspectives on this issue through the lenses of gender equality and Islamic thought. Using a library research method and secondary data sources, this study adopts a descriptive qualitative analysis approach. The findings highlight diverse scholarly views on women’s leadership. While many classical scholars express reservations, some contemporary scholars adopt a more accepting stance. From a gender equality perspective, Islam emphasizes that men and women possess rights and responsibilities and upholds principles of justice for all individuals, irrespective of gender. While differing opinions persist, women today contribute actively in various fields, often based on competence rather than gender. For Generation Z, their distinctive characteristics provide potential for leadership. Leadership often starts with self-leadership, evolving gradually to encompass broader responsibilities. Effective leadership is portrayed as a developmental process rather than an immediate attainment of high-ranking roles.